1989
DOI: 10.1152/jappl.1989.66.2.949
|View full text |Cite
|
Sign up to set email alerts
|

Physiological factors associated with the lower maximal oxygen consumption of master runners

Abstract: We examined the hemodynamic factors associated with the lower maximal O2 consumption (VO2max) in older formerly elite distance runners. Heart rate and VO2 were measured during submaximal and maximal treadmill exercise in 11 master [66 +/- 8 (SD) yr] and 11 young (32 +/- 5 yr) male runners. Cardiac output was determined using acetylene rebreathing at 30, 50, 70, and 85% VO2max. Maximal cardiac output was estimated using submaximal stroke volume and maximal heart rate. VO2max was 36% lower in master runners (45.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
2

Year Published

1991
1991
2012
2012

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 12 publications
4
50
2
Order By: Relevance
“…As previously reviewed, some investigators have observed age-related decreases in SVmax in NA and ET maies and females (205,222). According to the Frank-Starling mechanism, decreases in SVmax may result from decreases in diastolic filling (and thus, preload).…”
Section: Age-related Changes In Svmax I)mentioning
confidence: 91%
See 4 more Smart Citations
“…As previously reviewed, some investigators have observed age-related decreases in SVmax in NA and ET maies and females (205,222). According to the Frank-Starling mechanism, decreases in SVmax may result from decreases in diastolic filling (and thus, preload).…”
Section: Age-related Changes In Svmax I)mentioning
confidence: 91%
“…Both QMX and maximal snoke volume (SVmax) are signifcantly larger in younger (7, 222,234) as weii as i n younger and older ET fernales (205), compared to age and gender-matched nonnally active (NA) individuals. Penp heral adaptations in active skele t ai muscle also play an important role in the increase in V0,rna.x as a result of endurance training.…”
Section: Introductionmentioning
confidence: 86%
See 3 more Smart Citations